HUBUNGAN KELENGKAPAN PENGISIAN DISCHARGE SUMMARY RAWAT INAP DENGAN MUTU REKAM MEDIS - Elysa Rahmatillah; Mochamad Malik Ibrahim (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Some health care facilities regarding medical resumes are still often incomplete, one of which is at Aisyiyah Siti Fatimah Sidoarjo Hospital, where the completeness of medical record files has not yet reached 100% complete. This study aims to analyze the relationship between the completeness of the inpatient discharge summary and the quality of medical records. Methods: This type of research uses quantitative analytical correlation, with a cross sectional approach, the number of samples used is 164 in the inpatient discharge summary form, the sampling used is consecutive sampling. And using a research instrument check list sheet and data analysis using the chisquare test. Results: Research obtained on the discharge summary of hospitalization with an incomplete category of 77.4%. The quality of medical records with the category is quite good 86.0%, there is a relationship with a Pvalue of 0.000. Conclusion: From the results of the study that there is still an incomplete inpatient discharge summary, and the quality of medical records is quite good. This shows that there is a relationship between the completeness of the inpatient discharge summary and the quality of medical records, it is advisable to make a special SOP regarding the completeness of the discharge summary. Keywords: Discharge Summary, Completeness, Quality of Medical Records